Batik Motif “Sulur Harapan”: Data Visualization from Mathematical Model Simulation of Skin Cancer in South Sulawesi Province - Syafaatullah, Muhammad Rashif; Hisam, Salman Ibnu; Multazam, Akhmad Faris; Sugiyanto, Sugiyanto (Proceeding International Conference on Religion, Science and Education, 2026)
As part of Indonesia’s cultural heritage, batik continues to evolve through the integration of art and research. This study developed the “Sulur Harapan” batik motif based on data visualization obtained from a SEIR mathematical model simulation of skin cancer spread in South Sulawesi Province. To identify the dynamic patterns of disease spread and trends in the number of individuals in each population class, epidemiological data related to skin cancer cases affected by ultraviolet exposure were analyzed using mathematical modeling methods. The simulation results show that variations in the recovery rate play an important role in suppressing the number of infected people, and an increase in the recovery rate significantly accelerates the development of the disease. Philosophically, the dynamic patterns generated from this simulation are translated into vine motifs, which are symbols of growth, balance, and hope. This motif not only serves as an aesthetic work but also functions as a visual educational tool to inform people about the risks and ways to prevent skin cancer. Therefore, the “Sulur Harapan” batik serves as a way to integrate culture, science, and public health using a mathematical modeling approach.